TEACHING READING SKILLS IN IAIN SULTAN AMAI GORONTALO - Hasan, Jhems Richard (Irfani, 2014)
The importance of reading in IAIN Sultan Amai Gorontalo cannot be denied. Tomake the students fit nationally and internationally, their reading skills must beof an advanced level. If reading skills are improved, learners will be able toutilize maximum resources for acquiring knowledge and information, and it willchange the whole educational scenario of the Institute. So, the present study onâAn Evaluation of the Teaching of Reading Skills in IAIN Sultan AmaiGorontaloâ is of great importance. Considering the importance of this research,some attempts should be done in minimizing the problems faced by students andimproving the implementation of the teaching of reading for the sake of thedevelopment of studentsâ reading skill and pedagogy in IAIN Sultan AmaiGorontalo. Therefore, further research in this field is highly recommended.